Brief Report: Leg Length Inequality and Hip Osteoarthritis in the Multicenter Osteoarthritis Study and the Osteoarthritis Initiative. Issue 10 (27th September 2018) - Kim, Chan; Nevitt, Michael; Guermazi, Ali; Niu, Jingbo; Clancy, Margaret; Tolstykh, Irina; Jungmann, Pia M.; Lane, Nancy E.; Segal, Neil A.; Harvey, William F.; Lewis, Cora E.; Felson, David T.
Abstract : Objective: Studies suggest that persons with a leg length inequality (LLI) of ≥2 cm have an increased risk of developing knee osteoarthritis (OA) in that limb. The present study was undertaken to examine whether LLI also confers an increased risk of hip OA. Methods: Using long limb radiographs from subjects in the Multicenter Arthritis Study (MOST) and the Osteoarthritis Initiative (OAI), we measured LLI and scored hip radiographs that were obtained at baseline and 3–5‐year follow‐up. The associations of LLI of ≥1 cm and LLI of ≥2 cm with radiographic hip OA were examined cross‐sectionally and longitudinally, assessing risk in shorter limbs and longer limbs compared to limbs from subjects with no LLI. We carried out logistic regression analyses with generalized estimating equations and adjusted for age, sex, body mass index, height, and cohort of origin. Results: There were 1, 966 subjects from the MOST and 2, 627 subjects from the OAI. Twelve percent had LLI of ≥1 cm and 1% had LLI of ≥2 cm. For LLI ≥1 cm, the adjusted odds ratio for prevalent hip OA in the shorter leg was 1.47 (95% confidence interval [95% CI] 1.07–2.02) and for LLI ≥2 cm, it was 2.15 (95% CI 0.87–5.34). For LLI ≥1 cm, the odds of incident hip OA in the shorter leg were 1.39 (95% CI 0.81–2.39) while for LLI ≥2 cm, they were 4.20 (95% CI 1.26–14.03). We found no increased risk of hip OA in longer limbs. Conclusion: Our findings suggest that, as with knee OA, legs that are at least 2 cm shorter than the contralateral leg are at increased risk of hip OA.